Soul Liberty : The Evolution of Black Religious Politics in Postemancipation Virginia - Turner, Nicole Myers (Book collections on Project MUSE., 2020)
"That churches are one of the most important cornerstones of black political organization is a commonplace. In this history of African American Protestantism and American politics at the end of the Civil War, Nicole Myers Turner challenges the idea of always-already-politically engaged black churches. Using local archives, church and convention minutes, and innovative Geographic Information Systems (GIS) mapping, Turner reveals how freedpeople in Virginia adapted strategies for pursuing independent churches, religious freedom, political engagement, and justice to the evolving landscape of emancipation"--